2020
DOI: 10.3390/jcm9093029
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 Emergency on Health Professionals: Burnout Incidence at the Most Critical Period in Spain

Abstract: Background: The health profession is a burnout producer due to the continuous contact with pain and suffering. In addition, excessive workloads can generate stress and psychological distress. Objectives: The aim of this study was to determine the degree of burnout and its main triggers in health professionals in Spain at the most critical period of the COVID-19 emergency. Method: A quantitative research was developed through a simple random sampling in different Spanish hospitals through the period of greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
97
3
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 102 publications
11
97
3
11
Order By: Relevance
“…Our study showed that 87.2% of the participants reported their level of stress and/or anxiety increased in their work because of not having the basic supplies for their personal protection. This is one of the reasons why the levels of death anxiety and burnout were elevated, as also reported in previous studies [5,21].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study showed that 87.2% of the participants reported their level of stress and/or anxiety increased in their work because of not having the basic supplies for their personal protection. This is one of the reasons why the levels of death anxiety and burnout were elevated, as also reported in previous studies [5,21].…”
Section: Discussionsupporting
confidence: 83%
“…For example, a lot of research is being done concerning other occupations such as health workers, teachers, etc. [5,[55][56][57][58][59][60][61][62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Spain, risk factors associated to psychological distress and the presence of intensive and severe negative emotions in healthcare professionals included the lack of enough PPE under working exposure, non-existent or contradictory work protocols, working 12–24 h, or being worried that a family member could be infected by the virus [ 5 , 8 , 33 ]. Moreover, social isolation, uncertainty, reluctance to work, or considering absenteeism were also frequently reported by Spanish healthcare professionals [ 28 ].…”
Section: Discussionmentioning
confidence: 99%